2018
DOI: 10.1159/000493801
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Endovascular Thrombectomy for Acute Ischaemic Stroke in Anticoagulated Patients Ineligible for Intravenous Thrombolysis

Abstract: Background/Aim: Endovascular thrombectomy may be performed in anticoagulated patients taking vitamin-K antagonists (VKA) or direct-acting oral anticoagulants (DOAC) in whom the use of intravenous tissue plasminogen activator (tPA) is contraindicated. We aimed to investigate the efficacy and safety of mechanical thrombectomy specifically in anticoagulated patients ineligible for thrombolysis. Methods: We performed a retrospective analysis of a prospectively collected database of consecutive ischaemic stroke pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
(26 reference statements)
7
20
1
Order By: Relevance
“…We found that therapeutic anticoagulation in AF patients at the time of stroke did not adversely influence outcome. This finding is similar to several studies, including thrombolysis-ineligible patients [23][24][25][26][27] .…”
Section: Discussionsupporting
confidence: 92%
“…We found that therapeutic anticoagulation in AF patients at the time of stroke did not adversely influence outcome. This finding is similar to several studies, including thrombolysis-ineligible patients [23][24][25][26][27] .…”
Section: Discussionsupporting
confidence: 92%
“…With regards to technical efficacy of ET, if reported, all studies showed similar reperfusion rates in OAC and non-OAC patients as in our GSR-ET cohort [2,5,9,11,16,19,21,22]. Nevertheless, the reperfusion rates were distributed heterogeneously among the different studies ranging from 64 to 93% [2,5,9,11,16,19,21,22]. Additionally, one study compared ET in VKA and NOAC patients and reported on better reperfusion rates among NOAC patients [12] which was not reflected by our data showing similar reperfusion rates among OAC and non-OAC patients.…”
Section: Discussionsupporting
confidence: 68%
“…Most studies published retrospectively collected data, but four studies were prospective cohort studies [2, 5, 9-17, 19, 21, 22]. With regards to technical efficacy of ET, if reported, all studies showed similar reperfusion rates in OAC and non-OAC patients as in our GSR-ET cohort [2,5,9,11,16,19,21,22]. Nevertheless, the reperfusion rates were distributed heterogeneously among the different studies ranging from 64 to 93% [2,5,9,11,16,19,21,22].…”
Section: Discussionmentioning
confidence: 69%
“…To date, it has been a matter of controversy if EVT in AIS with prior anticoagulant treatment carries a major risk of bleeding. It is essential to select the best therapeutic approach in this subset of patients, because despite best medical treatment with anticoagulation 1-3% of patients will develop strokes annually (5).…”
Section: Introductionmentioning
confidence: 99%